Dental age estimation in a group of Kenyan children using Willems’ method: a radiographic study - Eunice Njeri Kihara; Peter Gichangi; Helen M. Liversidge; Fawzia Butt; Gichambira Gikenye (Annals of Human Biology, 2017)
Background: Radiographic study of developing teeth provides a reliable indication of chronological age. In Kenya, dentists are often required to estimate age. However, there is a paucity of publications on the performance of dental age estimation methods. Aim: To determine the accuracy of Willems’ method of dental age estimation. Subjects and methods: A cross-sectional study was done at The University of Nairobi Dental Hospital. Panoramic radiographs of children aged 3.00–16.99 years old were studied. Dental age was estimated according to Willems’ method and compared to chronological age and the difference compared to zero using a t-test. Results: Radiographs of 187 (47%) females and 214 (53%) males were analysed. Willems’ method significantly over-estimated the mean overall age by –0.24 ± 1.17 years (p < .000). Age was over-estimated in girls by –0.10 ± 1.18 years (p = .254); however, age in boys was significantly over-estimated by –0.37 ± 1.14 years (p < .000). Conclusions: Willem’s model over-estimated dental age slightly and the method performed better in estimating the age of girls compared to boys. The majority of the children had their age estimated within 1 year of their chronological age. This suggests that Willems’ method is suitable for estimating the ages of individual children in Kenya.